2016
DOI: 10.1093/pm/pnw096
|View full text |Cite
|
Sign up to set email alerts
|

Using Random Forest Models to Identify Correlates of a Diabetic Peripheral Neuropathy Diagnosis from Electronic Health Record Data

Abstract: Random forest modeling can determine likelihood of a DPN diagnosis. Further validation of the random forest model may help facilitate earlier diagnosis and enhance management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…An extremely important finding from our study, that is consistent with recent reports in diabetic neuropathy, 79,80 is the association between comorbidity and CIN. The SCQ score assesses not only the number but the impact of comorbidities on an individual.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An extremely important finding from our study, that is consistent with recent reports in diabetic neuropathy, 79,80 is the association between comorbidity and CIN. The SCQ score assesses not only the number but the impact of comorbidities on an individual.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of demographic characteristics, consistent with the risk factors for CIN noted above, as well as risk factors associated with painful diabetic neuropathy, 7982 survivors with CIN were older and had a lower annual household income.…”
Section: Discussionsupporting
confidence: 58%
“…It is worth noting that DM complications are far less common and severe in people with well-controlled blood glucose levels. Many of those complications have been studied through machine learning and data mining applications [78], [79], [80], [81], [82], [83], [84], [85], [87], [88], [89], [90], [92], [94], [95], [96], [97].…”
Section: Dm Through Machine Learning and Data Miningmentioning
confidence: 99%
“…Similarly, in the case of neuropathy, DuBrava et al used Random Forest (RF) in order to select specific features targeting prediction of diabetic peripheral neuropathy (DPN) [83]. Based on relevance, the features chosen were Charlson Comorbidity Index score (100%), age (37.1%), number of pre-index procedures and services (29.7%), number of pre-index outpatient prescriptions (24.2%), number of pre-index outpatient visits (18.3%), number of pre-index laboratory visits (16.9%), number of pre-index outpatient office visits (12.1%), number of inpatient prescriptions (5.9%), and number of pain-related medication prescriptions (4.4%).…”
Section: Dm Through Machine Learning and Data Miningmentioning
confidence: 99%
“…It has been shown that random forest performs equally well or better than other methods on a diverse set of problems. It has been widely used in classification problems as diverse as bioinformatics 16 , medicine 17 , transportation safety 18 and customer behavior 19 .…”
Section: Random Forestmentioning
confidence: 99%